2015
DOI: 10.1016/j.juro.2014.08.110
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Accelerates the Regeneration of Ureteral Function in a Murine Model of Obstructive Uropathy

Abstract: Erythropoietin treatment significantly promoted functional recovery of the ureter after obstruction removal. Erythropoietin may be a helpful strategy for ureteral motility recovery and hydronephrosis resolution in ureteral obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(25 reference statements)
2
8
0
Order By: Relevance
“…EPO has previously been demonstrated to improve intestinal dysmotility by increasing the force of contraction in response to acetyl choline administration (15). Our group has shown a similar improvement of ureteral motility following EPO administration in a mouse model of ureteral obstruction (4). In this study using non-obstructed ureteral tissue, we demonstrate that EPO decreases ureteral contraction force in "normal" uninjured human ureteral tissue.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…EPO has previously been demonstrated to improve intestinal dysmotility by increasing the force of contraction in response to acetyl choline administration (15). Our group has shown a similar improvement of ureteral motility following EPO administration in a mouse model of ureteral obstruction (4). In this study using non-obstructed ureteral tissue, we demonstrate that EPO decreases ureteral contraction force in "normal" uninjured human ureteral tissue.…”
Section: Discussionsupporting
confidence: 68%
“…Partial or complete obstruction results in ureteral dysfunction, manifesting as the cessation of peristaltic activity and urine transport from the kidney on the affected side to the bladder. Previous work has shown that the return of peristalsis to pre-obstruction levels is significantly delayed following obstruction reversal and resolution of hydronephrosis, suggesting that negative effects on urine drainage and possibly kidney function are prolonged (4). An improved understanding of mechanisms that drive ureteral peristalsis as well as those elicited by currently used pharmacological approaches to manipulate ureteral function is required for the development of more effective approaches to regulate ureteral peristalsis preand/or post-operatively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations